Techno-economic and sustainability assessment of the power to MeOH processes: The present and future perspective - Ali Pakdel; Reza Eslamloueyan (Heliyon)
This study presents a comprehensive analysis of a Power-to-Methanol (PtM) process, which converts CO2 and H2 derived from electrolysis of water into methanol (MeOH) using renewable energy sources. The process is analyzed for its technical, economic, and environmental aspects, focusing on production costs and the minimum selling price of MeOH. The simulation results show an energy efficiency of 56 % in the optimal state, with a CO2 consumption of 1.4 kg-CO2/kg-MeOH. Economic evaluations for 2023 indicate production costs of US$ 631 and 643 for PtM processes equipped with membrane and amine absorption technologies, respectively. The study also predicts the cost of production and minimum selling price of MeOH from 2023 to 2030 based on the trends of electrolyzer capital investment and renewable resource prices. The results provide valuable insights for the development and evaluation of sustainable MeOH production processes.